Liquid filtration. - Cheremisinoff, Nicholas P. (Butterworth-Heinemann, 1998)
A review of liquid filtration in the chemical process and allied industries. Interpretations of the phenomenological observations of the hydrodynamics of filtration are given in the hopes of establishing more theoretical and generalized bases of design methodology. Specific design and selection criteria are reviewed, and typical industrial problems and their solutions are presented.